‘Tightness’, recognition and penal power - Crewe, Ben (Punishment & society, 2021)
Prison scholarship has tended to focus on the pains and frustrations that result from the use and over-use of penal power. Yet the absence of such power and the subjective benefits of its grip are also worthy of attention. This article begins by drawing on recent literature and research findings to develop the concept of ‘tightness’ beyond its initial formulation. Drawing primarily on data from a study of men convicted of sex offences, it goes on to explain that, in some circumstances, the reach and hold of penal power are not experienced as oppressive and undesirable, and, indeed, may be welcomed. Conversely, institutional inattention and an absence of grip may be experienced as painful. Prisons, then, can be ‘loose’ or ‘lax’ as well as ‘tight’. The article then discusses the different ways in which prisons exercise grip, and, in doing so, recognise or misrecognise the subjectivity of the individual prisoner. It concludes by identifying the connections between this ‘ground-up’ analysis of the relative legitimacy of different forms of penal intervention and recent discussions in penal theory about the proper role of the state in communicating censure and promoting personal repentance and change.